Multidrug-Resistant Strains of Salmonella enterica serotype typhi are Genetically Homogenous and Coexist with Antibiotic-Sensitive Strains as Distinct, Independent Clones - Thong, Kwai Lin; Bhutta, Z.A.; Pang, T. (Elsevier, 2000)
Objective: The goal of this study was to report the molecular analysis of antibiotic-sensitive and multidrug-resistant (MDR) strains of Salmonella typhi, using pulsed-field gel electrophoresis (PFGE), with a particular emphasis on the coexistence of these strains in a typhoid-endemic region of Karachi, Pakistan. Methods: One hundred isolates of S. typhi in humans (50 MDR and 50 antibiotic-sensitive isolates) from sporadic cases of typhoid fever were analyzed by Vi-phage typing, antibiograms and PFGE. Results: The MDR S. typhi strains were resistant to ampicillin, chloramphenicol, and trimethoprim-sulfamethoxazole. Analysis by PFGE showed that 50 MDR isolates of S. typhi had a single, homogenous PFGE profile, which was distinctly different from that of 50 antibiotic-sensitive isolates obtained in the same time frame from the same area. This latter group of isolates showed much greater diversity of PFGE profiles, as has been observed in other endemic regions. Conclusions: Multidrug-resistant and antibiotic-susceptible strains of S. typhi can coexist in endemic areas as epidemiologically independent pathogens and are not in competition for continued persistence and transmission.